2009 16th Asia-Pacific Software Engineering Conference 2009
DOI: 10.1109/apsec.2009.64
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the State of User Involvement in Practice

Abstract: Involving users in software development has been reported to increase the probability of product and project success, as well as user satisfaction. User involvement can occur in the tasks of several different organizational functions, including a dedicated user-centered team. This article presents the results of a case study conducted to understand the current state of user involvement practice in a company producing software solutions for consumers, enterprises, and service providers. The company has recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
2
4
0
1
Order By: Relevance
“…Other studies (e.g. [7], [9], [18]) support our findings, what makes us confident that the identified problems are real. Ensuring construct validity for empirical studies of software developers is always a complex task, specifically as such studies typically require the researcher to abstract from observed behavior or gathered information.…”
Section: B Limitationssupporting
confidence: 89%
See 1 more Smart Citation
“…Other studies (e.g. [7], [9], [18]) support our findings, what makes us confident that the identified problems are real. Ensuring construct validity for empirical studies of software developers is always a complex task, specifically as such studies typically require the researcher to abstract from observed behavior or gathered information.…”
Section: B Limitationssupporting
confidence: 89%
“…Heiskari and Lehtola [7] investigate user involvement in practice without focusing on a specific development lifecycle phase, and identify several challenges which are confirmed by our study. First, similarly to our results the authors found that user information is scattered, unorganized, and difficult to access (Hypothesis 1), and that there is no clear and common process on understanding users (Hypothesis 4).…”
Section: Related Worksupporting
confidence: 57%
“…According to Bano and Zowghi (2015), "the most prominent problems caused by user involvement are communication problems and misunderstandings between the users and the development teams leading to all kinds of conflicts." Conflicts always make their way between the team and users, therefore the management must adopt conflict management strategies to handle them effectively (Heiskari and Lehtola, 2009). Melo (2013) found that problems are caused by not being "able to manage the conflicts regarding the work procedures, leading to turnover and decreased productivity in the short term (teams were unable to deliver for a while), as well as loss in both knowledge and team overhead after the turnover."…”
Section: Relationship Conflicts "Involve Disagreements Amongmentioning
confidence: 99%
“…The development of novel software products, as well as the improvement of existing ones, can deeply benefit from the involvement of users in requirements engineering (RE) activities (Bano and Zowghi, 2015). Getting feedback from the user base has been recognised to lead to increased usability, improved satisfaction (Bakalova and Daneva, 2011), better understanding of requirements (Hanssen and Faegri, 2006), and creation of long-term relationships with customers (Heiskari and Lehtola, 2009). User feedback can take implicit and explicit forms, and different means are available to collect this information.…”
Section: Introductionmentioning
confidence: 99%